Missing Rings in Pinus halepensis – The Missing Link to Relate the Tree-Ring Record to Extreme Climatic Events - Novak, Klemen; de Luis, Martin; Saz, Miguel A.; Longares, Luis A.; Serrano-Notivoli, Roberto; Raventós, Josep; Čufar, Katarina; Gričar, Jožica; Di Filippo, Alfredo; Piovesan, Gianluca; Rathgeber, Cyrille B. K.; Papadopoulos, Andreas; et al. (Frontiers in Plant Science, 2016)
Climate predictions for the Mediterranean Basin include increased temperatures, decreased precipitation, and increased frequency of extreme climatic events (ECE). These conditions are associated with decreased growth of trees and their increased vulnerability to pests and diseases. The anatomy of tree rings is responsive to these environmental conditions. Quantitatively, the width of a tree ring is largely determined by the rate and duration of cell division by the vascular cambium. In the Mediterranean climate, cambial cell division may occur throughout almost the entire year. Alternatively, cell division may stop during relatively cool and dry winters, only to resume in the same year with milder temperatures and increased availability of water. Under particularly adverse conditions, no xylem may be produced in parts of the stem, resulting in a missing ring (MR), which can link tree-ring anatomy to the occurrence of extreme events. A dendrochronological network of Pinus halepensis, a widespread tree species in the Mediterranean basin, was used to determine the relationship of MR to ECE. The network consisted of 113 sites throughout its distribution range. Binomial logistic regression analysis of 2595 MR series determined that MR increased in frequency with increased cambial age. Spatial analysis indicated that the geographic areas of southeastern Spain and northern Algeria contained the greatest frequency of MR. Further regression analysis indicated that the relationship of MR to total monthly precipitation and mean temperature was non-linear. In this first determination of climatic influences on MR, the formation of MR was most strongly associated with the combination of monthly mean temperature above 10°C from previous October till current February and total precipitation below 50 mm from previous September till current May. This conclusion is global and can be applied to every site across the distribution area. Rather than simply being a complication for dendrochronology, MR formation is a fundamental response of trees to adverse environmental conditions. The demonstrated relationship of MR formation to ECE across this dendroclimatic network in the Mediterranean basin shows the potential of MR analysis to reconstruct the history of past climatic extremes and to predict future forest dynamics in a changing climate.